2014
DOI: 10.1002/ijop.12049
|View full text |Cite
|
Sign up to set email alerts
|

How personal resources predict work engagement and self-rated performance among construction workers: A social cognitive perspective

Abstract: PostprintCita bibliográfica / Cita bibliogràfica (ISO 690): LORENTE, Laura, et al. How personal resources predict work engagement and self-rated performance among construction workers: A social cognitive perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
60
0
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 22 publications
9
60
0
10
Order By: Relevance
“…Personal resources have been indentified as the most crucial determinants of work engagement together with job resources based on the JD-R model (Lorente et al 2014;Xanthopoulou et al 2009). Individuals high in self-efficacy are more inclined to invest energy, feeling and times in their practice work (Salanova et al 2011;Vera et al 2014;Xanthopoulou et al 2013).…”
Section: The Three-path Mediating Effect Of Self-efficacy and Work Enmentioning
confidence: 98%
“…Personal resources have been indentified as the most crucial determinants of work engagement together with job resources based on the JD-R model (Lorente et al 2014;Xanthopoulou et al 2009). Individuals high in self-efficacy are more inclined to invest energy, feeling and times in their practice work (Salanova et al 2011;Vera et al 2014;Xanthopoulou et al 2013).…”
Section: The Three-path Mediating Effect Of Self-efficacy and Work Enmentioning
confidence: 98%
“…Another study (Day et al, 2006) found that beginning teachers' main focus is on developing work efficacy and commitment, middle-aged teachers focus on balancing work and personal life while 25% of teachers become demotivated from their work, and high school teachers in their senior years lose work motivation even more. On the other hand, regardless of working age several studies (Lorente et al, 2014, Lee & Ok, 2015 have found strong correlation between work motivation and working conditions and resources. According to Assor et al (2002) schools' resources and structure can limit teachers' chances to provide students with appealing and significant tasks.…”
Section: The Effect Of Age and Subjectmentioning
confidence: 97%
“…Both theory (e.g., Ajzen & Fishbein, 1980; Godin & Kok, ) and empirical research (e.g., Bagozzi, ; Cooke & Sheeran, 2004; Gollwitzer & Sheeran 2006) have shown the connection between appraisal, intentionality, and behavior. With the advent of appraisal models being used in employee engagement studies (e.g., Lin, Wu, Chen, & Chen, ; Lorente, Salanova, Martinez, & Vera, ; Nimon & Zigarmi, ; Roberts & Zigarmi, ; Zigarmi & Roberts, ), the WII‐SF has the opportunity to support empirical research that seeks to examine intentionality as a proxy for behaviors that are theoretically related to the state of employee engagement as formed through the cognitive appraisal of the work environment. The WII‐SF may also contribute to future research which seeks to test theory that seeks to explain outcomes associated with employee engagement.…”
Section: Contributions To Theory and Literaturementioning
confidence: 99%